Nonsurgical removal of separated gutta percha and granulation tissue from the periapical area using an aspiration irrigation technique - Shanmugam Jaikailash; Mahendran Kavitha; Kannan Gokul (Wolters Kluwer Medknow Publications, 2012)
Pulpal diseases progress to periapical lesions. The incidence of cysts and granulomas within periapical lesions are 55% and 70.07%, respectively. It is accepted that all inflammatory periapical lesions should be initially treated with conservative nonsurgical procedures. Studies have reported a success rate of up to 85% after endodontic treatment of teeth with periapical lesions. The various options for the removal of obturating material are K-files or H-files, gutta percha solvent, combination of paper points and gutta percha solvent, rotary instruments, retreatment files, heat transfer devices, heat carrier tips, ultrasonic tips and soft tissue laser. In the present case, we removed the gutta percha using K-files and H-files. The various methods of removing detached gutta percha are K-files and H-files, heat carrier tips or periapical surgery. Various methods can be used in the nonsurgical management of periapical lesions: The conservative root canal treatment, decompression technique, active nonsurgical decompression technique, aspiration-irrigation technique, calcium hydroxide methods, lesion sterilization and repair therapy and the apexum procedure. In the present case, we removed the gutta percha using K-files and H-files and we followed the aspiration-irrigation technique as a line of management. This case report describes an aspiration-irrigation technique achieved through the root canal space, which might hasten osseous regeneration, thereby eliminating the need for periapical surgery.